Adaptasi Pakan Buatan Pada Beberapa Jenis Ikan Endemik Jambi Sebagai Tahap Awal Domestikasi - Pangentasari, Dwinda; Harianto, Eko; Rahmadiah, Triayu; Nurjanah, Lilis; Nugrahawati, Anis; Mulyani, Rahma; Lestari, Sekar Yunita (Universitas Batangahari Jambi, 2025)
This study was conducted as an initial step in the domestication process of endemic fish in Jambi Province through an artificial feed adaptation approach. In addition, there is little data and research in Jambi Province that systematically discusses and tests artificial feed adaptation as part of domestication. This study aims to analyze the feed adaptation response in the cultivation of sepat fish (Trichopodus pectoralis), tambakan fish (Helostoma temminckii), and betok fish (Anabas testudineus) originating from the public waters of Kota Karang Village, Kumpeh Ulu District, Muaro Jambi as the initial stage of domestication. This study used a completely randomized design) with three treatments and three replicates. The treatments applied were different types of endemic Jambi fish, including sepat fish (T. pectoralis, treatment A), tambakan fish (H. temminckii, treatment B), and betok fish (A. testudineus, treatment C). The fish used in this study were wild fish obtained from public waters in Kota Karang Village, Kumpeh Ulu District, Muaro Jambi Regency. The average initial weight and length of sepat fish were 3.37±0.98 g and 6.32±1.52 cm, tambakan fish 7.65±0.74 g and 8.17±0.59 cm, and betok fish 8.03±1.13 g and 7.57±1.14 cm. Maintenance was carried out for 4 weeks, during which the test fish were fed artificial feed or commercial feed (39% protein). The feeding method was Ad-restricted. Feeding frequency is three times a day, namely in the morning, afternoon, and evening. The results of the study show that the SR value produced is 100% for all treatments. The highest PBM value is found in treatment A (sepat fish) at 1.34 g and the lowest PBM value is found in treatment C (betok fish) at 0.82 g. The highest PPM value was found in treatment A (sepat fish) at 1.12 cm, and the lowest PPM value was found in treatment B (tambakan fish) at 0.39 cm. The highest LPS value was found in treatment C (betok fish) at 6.40%/day, and the lowest LPS value was found in treatment A (sepat fish) at 3.54%/day. In general, the water quality parameters of the maintenance medium were suitable for the growth and survival of freshwater fish.